THE USE OF VOICEOVER CHALLENGES ON TIKTOK AS ESL SPEAKING ACTIVITIES - Chuah, Kee Man (2021)
The video-sharing social network, TikTok, has gained global fame for its virality and entertainment value. However, over the last two years, more micro-learning contents have been uploaded on the platform. Voiceover challenges are one of those contents in which users need to perform a voiceover on a given text. For English as a Second Language (ESL) learners, this provides authentic opportunities to practise their speaking skills. In this study, a total of 60 students were told to take part in 12 voiceover challenges for two months. They were required to record every challenge and upload the recordings to a database. They were then given an online questionnaire covering items related to their learning experience and views on the challenges. The results showed that the students were very positive about the learning experience as they could practice turn-taking, pronunciation, and intonation. Moreover, they mentioned that the challenges motivated them to use the language more often. A review of their recordings revealed that many of them showed improvements in their pronunciation. The outcome of this study sheds light on the usefulness of TikTok in English language learning, particularly for ESL learners who lack confidence in speaking.